Assessment of serum, dietary zinc levels, and other risk factors during the third trimester among pregnant women with and without pregnancy-induced hypertension: a case-control study - El Bilbeisi, Abdel Hamid; Abo Khosa, Sahar M.; Taleb, Mahmoud H.; El Afifi, Amany M. (Frontiers in Nutrition, 2023)
Background: This study assessed serum, dietary zinc levels and other risk factors during the third trimester among pregnant women with and without pregnancy-induced hypertension (PIH). Methods: This case-control study was conducted in 2022, in the three main Obstetrics and Gynecology departments in Gaza Strip, Palestine. One hundred sixty pregnant women, during the third trimester, aged 20 ≥ years, were selected using a convenient sampling method. Data were obtained using an interview-based-questionnaire, food frequency questionnaire, anthropometric measures and biochemical tests. Statistical analysis was performed using SPSS version 24. Results: The participants’ mean age was 30.7±5.6 years. 47(58.8%) of cases and 6(7.5%) of controls were insufficiently active; and the mean of blood pressure (mmHg) was 133.3±11.9/85.11±10.0 for cases and 112.8±9.5/68.02±7.2 for controls with significant differences between the two groups (P=<0.005). The mean serum zinc level (μg/dl) was 67.15±16.5 for cases and 68.45±18.0 for controls without significant differences between the two groups (P=0.636). For newborns, the mean birth weight (gram) was 2904.6±486 for cases, and 3128.3±501 for controls, and the mean Apgar score was 8.03±0.62 for cases and 8.30±1.17 for controls, with significant differences between the two groups (P=<0.005). Furthermore, 43(53.8%) of cases have a family history of hypertension; 5(6.2%) were primiparous; 19(23.8%) had previous caesarian section; 33(41.2%) had a history of preeclampsia; and 62(77.5%) had oedema, with significant differences between the two groups (P=<0.005). Additionally, the total dietary zinc daily intake (mg/day) was 4.15±2.10 for cases and 4.88±3.02 for controls, with significant differences between the two groups (P=0.041). After adjustment for confounding variables, participants in the case group have higher odds of having low total zinc dietary intake, compared to those in the control group [OR = 1.185, 95% CI = (1.016-1.382), P = 0.030]. Conclusions: The current study showed the main risk factors of PIH among pregnant women in the Gaza Strip, Palestine. Furthermore, low maternal dietary zinc intake was associated with a high level of PIH. Moreover, having PIH could increase the risk of low birth weight and low Apgar score. Therefore, reducing the main risk factors of PIH could reduce the adverse effect on both mother and birth outcomes.